Mass media and national development : the role of Information in the developing countries - "Schramm, Wilbur" (Paris, 1964)
More than seventy countries are now trying to accomplish what Julius Nyerere of Tanganyika called the "terrible ascent" from traditional society to economic and social modernity. How much easier would this climb be if they were to apply the full strength of modern communication to the task? this is the question posed by this challenging book, which is on case studies and research from many countries, and is published jointly by UNESCO and the Stanford University Press.
Keywords: Communication Social aspects